The difference in symmetry of the enamel defects in celiac disease versus non-celiac pediatric population - Viviana Marisa Pereira Macho; Maria Conceição Antas de Barros Menéres Manso; Diana Maria Veloso e Silva; David José Casimiro de Andrade (Elsevier, 2020)
Background/purpose: Dental enamel defects are related to celiac disease and the dentists are in a perfect situation to identify and report suspected cases. The aim was to evaluate the symmetry of enamel defects in a pediatric Portuguese population with celiac disease and compare it with healthy controls. Materials and methods: a case-control study was performed in 80 patients with celiac disease and 80 healthy individuals aged 6-18 years old as controls. Data was collected by a questionnaire and clinical observation. Colour, type, and site of enamel defects were recorded and classified according to Aine criteria. Data analysis was performed, and any p-value <0.05 was considered significant. Results: Enamel defects were found in 55% of patients with celiac disease and 27.5% in the control individuals (p < 0.001). Grade I of Aine's classification was the most found in both groups, but it was higher in the celiac disease group, not only in the permanent dentition, but also in both dentitions with statistically significant difference (p = 0.002 and p = 0.001 respectively). Grade II was found only in the celiac disease group. It was observed that enamel defects in celiac disease were symmetric and the most affected teeth were the first permanent molars (p = 0.003) and the permanent incisors (p = 0.001). Conclusion: Symmetric dental enamel defects in population with celiac disease are more predominant than in general population. Therefore, individuals with enamel defects, especially those with symmetric lesions, should be well evaluated and the possibility of having celiac disease in the clinical history must be taken into account.